Effects of single dose of dexamethasone on patients with systemic inflammatory response - Cicarelli, Domingos Dias; Benseñor, Fábio Ely Martins; Vieira, Joaquim Edson (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Systemic inflamma- tory response syndrome (SIRS) is a very common condition among critically ill patients. SIRS, sep- sis, septic shock and multiple organ dysfunction syndrome (MODS) can lead to death. Our aim was to investigate the efficacy of a single dose of dexamethasone for blocking the progression of systemic inflammatory response syndrome. DESIGN AND SETTING: Prospective, randomized, double-blind, single-center study in a postopera- tive intensive care unit (Surgical Support Unit) at Hospital das Clínicas, Faculdade de Medicina, Universidade de São Paulo. METHODS: The study involved 29 patients with SIRS. All eligible patients were prospectively randomized to receive either a single dose of 0.2 mg/kg of dexamethasone or placebo, after SIRS was diagnosed. The patients were moni- tored over a seven-day period using Sequential Organ Failure Assessment score (SOFA). RESULTS: The respiratory system showed an improvement on the first day after dexametha- sone was administered, demonstrated by the improved PaO2/FiO2 ratio (p < 0.05). The cardiovascular system of patients requiring vasopressor therapy also improved over the first two days, with a better evolution in the dexamethasone group (p < 0.05). Non-surviv- ing patients presented higher lactate assays than did survivors (p < 0.05) during this period. CONCLUSIONS: Dexamethasone enhanced the effects of vasopressor drugs and evaluation of the respiratory system showed improvements (better PaO2/FiO2 ratio), one day after its ad- ministration. Despite these improvements, the single dose of dexamethasone did not block the evolution of SIRS.